U-shaped association between serum calcium and all-cause mortality in coronary heart disease with chronic kidney disease: evidence from two cohort studies in China and the United States - Shuling Su; Yongluan Lin; Weixin Ni; Haoxian Tang; Chuqi Gao; Xiulian Deng; Shiwan Wu; Yequn Chen; Xiaobin Ni (Renal Failure, 2025)
Background Chronic kidney disease (CKD), as a major risk factor for coronary heart disease (CHD), had a large fluctuation of serum calcium in clinical research. Our study aims to identify the association between serum calcium and all-cause mortality in CHD patients with CKD.Methods A retrospective cohort study was conducted, involving 2,286 participants from the CHD sub-cohort from the Eastern Guangdong Health and Disease Cohort Platform (EGHDCP) and 1,278 participants from National Health and Nutrition Examination Survey (NHANES) database. Cox proportional hazards regression models, stratified analysis with interaction, restricted cubic splines (RCS), and threshold effect analysis were applied to investigate the association between serum calcium and all-cause mortality of CHD with CKD.Results The association between serum calcium and all-cause mortality of CHD patients with CKD from EGHDCP-CHD exhibited an U-shaped curve in RCS, which was similar to be observed in NHANES cohort. In EGHDCP-CHD cohort, Cox regression models demonstrated that subjects in the lowest or the highest serum calcium group had a significantly higher risk of mortality. Besides, both cohorts showed similar inflection points in the threshold analysis. In EGHDCP-CHD cohort, the risk of all-cause mortality reduced by 9.73% with every 0.1 mmol/L increased in serum calcium (Hazard ratio (HR) = 0.027, 95% confidence interval (CI): 0.005-0.145, p < 0.001), while it increased by 30.46% when the serum calcium evaluated more than 2.27 mmol/L increased every 0.1 mmol/L (HR = 4.046, 95% CI: 1.143-14.319, p = 0.0302).Conclusion There was an U-shaped connection between serum calcium and all-cause mortality in CHD patients with CKD.